Identification and Analysis of Aux/IAA Family in Acer rubrum. (April 2021) - Zhu, Wenpeng; Zhang, Manyu; Li, Jianyi; Zhao, Hewen; Ge, Wei; Zhang, Kezhong
The phytohormone auxin are important in all aspects of plant growth and development. The Auxin/Indole-3-Acetic Acid ( Aux/IAA ) gene responds to auxin induction as auxin early response gene family. Despite the physiological importance of the Aux/IAA gene, a systematic analysis of the Aux/IAA gene in Acer rubrum has not been reported. This paper describes the characterization of Acer rubrum Aux/IAA genes at the transcriptomic level and Acer yangbiense Aux/IAA genes at the genomic level, with 17 Acer rubrum AUX/IAA genes (ArAux/IAA) and 23 Acer yangbiense Aux/IAA (AyAux/IAA) genes identified. Phylogenetic analysis shows that AyAux/IAA and ArAux/IAA family genes can be subdivided into 4 groups and show strong evolutionary conservatism. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to test the expression profile of ArAux/IAA genes in different tissues under indole-3-acetic acid (IAA) treatment. Most ArAux/IAA genes are responsive to exogenous auxin and have tissue-specific expression. Overall, these results will provide molecular-level insights into auxin metabolism, transport, and signaling in Acer species.